Evaluation of the Effect of Telmisartan on Gentamicin-Induced Nephrotoxicity in Rats - Reem Haj Darwish; Shadi Homs (Journal of Pharmacy and Nutrition Sciences, 2018)
Gentamicin (Gen) is widely used against serious infections, but its therapeutic use is limited due to its nephrotoxicity which causes acute renal failure. We aimed to evaluate the potential protective effect of highly selective angiotensin II (Ang II) type 1 (AT1) receptor blocker Telmisartan (Tel) on the renal damage generated by Gentamicin in rats. 36 Male Wistar rats were divided into six groups (6 rats each): Naive, Tel group (10 mg/kg/day orally for 7 days), control (1 ml/day 0.9% NaCl intraperitoneally i.p. for 7 days), Gen group (100 mg/kg/day i.p for 7 days), Gen + Tel 5 mg/kg/day concurrently for 7 days, Gen + Tel 10 mg/kg/day concurrently for 7 days. Concentrations of serum urea, serum creatinine, and renal reduced glutathione (GSH) levels were evaluated after treatment. Gen was observed to cause a severe nephrotoxicity, which was evidenced by an elevation of serum urea and creatinine levels which weren’t altered by simultaneous treatment with Tel. The oxidative stress caused by Gen demonstrated by a decrease in renal GSH level was significantly attenuated by Telmisartan (the higher dose). Conclusion: This study proves the nephrotoxicity caused by Gentamicin, and suggests that concurrent treatment with Telmisartan ameliorate oxidative stress induced by gentamicin without changes to serum urea and creatinine.